Perioperative Hypothermia in Adults in a Tertiary University Hospital: a cross-sectional analysis. - Silva, Wallace Andrino; Isadora Azevedo Medeiros do Nascimento; Maria Eduarda Pinheiro Gomes; Naíla Esther Gomes Fernandes; João Vicente Souza Santana; Aline Macêdo Pinheiro (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2025)
Background Perioperative hypothermia, defined as a core body temperature below 36°C, is a frequent complication in surgical patients, associated with adverse outcomes such as infections, cardiovascular events, and increased morbidity and mortality. This study evaluated the incidence of perioperative hypothermia, identified associated risk factors, and assessed prophylactic measures in a tertiary university hospital. Methods We conducted an observational, cross-sectional study of patients undergoing elective surgeries between February and May 2024. Tympanic temperature was measured at six perioperative time points, and clinical, demographic, and anesthetic data were collected. Statistical analysis included descriptive statistics and hypothesis testing, with significance set at p<0.05. Results A total of 91 patients were included, with a 92.3% incidence of hypothermia. Male sex was significantly associated with hypothermia (58.3% vs. 14.3%, p=0.043), while other factors, including ASA classification, obesity, and anesthetic type, showed no significant correlation. Temperature decreased most during the first hour post-induction, with median preoperative and end-of-surgery values of 36.3°C and 35.1°C, respectively. Prophylactic warming techniques were underutilized, with only 28.6% of patients receiving active warming. Conclusions The study revealed a high incidence of perioperative hypothermia, emphasizing the need for improved temperature management protocols and healthcare team education.